Português acadêmico para alunos internacionais : uma proposta da pragmática para a construção de módulos de ensino on-line - Gabbi, Vanessa Cardoso da Silva (2021)
Centered on the studies of Pragmatics, specifically on the concepts of Sociopragmatics and Pragmalinguistics (LEECH, 1983; THOMAS, 1983), and from the perspective of Van Dijk (1977) on speech acts, this thesis proposes two learning modules of the Brazilian Portuguese for Academic Purposes course Portuguese360, designed by Antunes (2020), which focuses on international students. Also based on Swales’ (1990) conception of genres, Biodata and Note Taking activities are developed through video classes and exercises, which demonstrate that language teaching, according to Pragmatics, allows students to develop significant pragmaticlinguistic competences. The first part of the thesis consists of the introduction, which explains the origin, contextualization, and justification of the work, followed by the theoretical foundation, which presents the main conceptual pillars for the development of the modules. The following chapters present the objectives of the study, the making of the Biodata and Note Taking modules and a detailed analysis and discussion of what was developed. Finally, the thesis is concluded by establishing that the studies of Pragmatics can provide the theoretical support for the acquisition of additional languages (LA) and must be taken into consideration in order to promote the development of not only linguistic but also pragmatic competences in LA students.